1999
DOI: 10.1023/a:1008353312410
|View full text |Cite
|
Sign up to set email alerts
|

Leukoencephalopathy in multiple myeloma: Two case reports

Abstract: The authors suggest that leukoencephalopathy is probably a direct cerebral expression of malignant gammopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Monoclonal gammopathy is frequently associated with a chronic progressive sensorimotor peripheral neuropathy. In contrast, involvement of the CNS in patients with monoclonal gammopathy has only been described in case reports [13,18–20] and smaller case series [11,12]. Although these suggest that demyelination in the CNS may occur in some patients with either IgG or IgM M‐protein, it is yet uncertain whether there is a clear association between circulating M‐proteins and pathological involvement of the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal gammopathy is frequently associated with a chronic progressive sensorimotor peripheral neuropathy. In contrast, involvement of the CNS in patients with monoclonal gammopathy has only been described in case reports [13,18–20] and smaller case series [11,12]. Although these suggest that demyelination in the CNS may occur in some patients with either IgG or IgM M‐protein, it is yet uncertain whether there is a clear association between circulating M‐proteins and pathological involvement of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The presumed target antigens are not exclusively expressed in the peripheral nervous system (PNS), but are also widely distributed in the CNS [8–11]. Generally, reports about CNS involvement in patients with monoclonal gammopathy are sparse, and previous MRI‐based studies demonstrated that only a subset of patients with monoclonal gammopathy display demyelinating lesions in the cerebral white matter [11–13]. Thus it remains largely unclear that why immunopathological effects of circulating M‐proteins, especially those with specific immunoreactivity against glycolipids, appear to be restricted to the PNS only.…”
Section: Introductionmentioning
confidence: 99%
“…These patients developed severe encephalopathy with seizures and mental status deterioration following treatment for multiple myeloma. 10 Methotrexate (used in Cases 3 and 4) has a welldocumented history of producing neurotoxic effects following administration. Within hours of a methotrexate dose, an aseptic meningitis has been shown to develop in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…The association between leukoencephalopathy and multiple myeloma is extremely rare, and to our knowledge, only two similar cases have been previously reported in patients with more advanced multiple myeloma . One case presented with cognitive complaints, paresthesia, sensory ataxia, and amyotrophy; the other case presented with headache, vertigo, disorientation, and asthenia.…”
Section: Discussionmentioning
confidence: 82%